Social Distancing and Risk Taking: Evidence from a Team Game Show - Jean-Marc Bourgeon; José De Sousa; Alexis Noir-Luhalwe (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine the risky choices of pairs of contestants in a popular radio game show in France. At one point during the COVID-19 pandemic the show, held in person, had to switch to an all-remote format. We find that such an exogenous change in social context affected risk-taking behavior. Remotely, pairs take far fewer risks when the stakes are high than in the flesh. This behavioral difference is consistent with prosocial behavior theories, which argue that the nature of social interactions influences risky choices. Our results suggest that working from home may reduce participation in profitable but risky team projects.
Keywords: C93; D81; D91; 330; COVID-19; social distancing; social pressure; decision making; risk